2002
DOI: 10.1155/2002/493296
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Salmeterol 50 µg Bid to Anticholinergenic Treatment in Patients with COPD: A Randomized Placebo Controlled Trial

Abstract: BACKGROUND:In the past, the role of long-acting beta 2 -agonists in chronic obstructive pulmonary disease (COPD) relative to other agents has been unclear. OBJECTIVES: To compare the effect of adding salmeterol (50 µg bid) or placebo to concurrent anticholinergic therapy on symptom scores, quality of life, prebronchodilator lung function and exacerbations in patients with moderately severe COPD. METHODS:This was a double-blind, randomized, parallelgroup study in patients aged 40 years or older receiving antich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Although LABAs reduced the use of rescue medication in the majority of studies, the efficacy of these agents on dyspnoea is not consistent across trials and significant benefits on exercise tolerance have not been well described (table 1) [9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, a recent, small-scale (23 patients), mechanistic, crossover study showed that salmeterol significantly reduced hyperinflation, with consequent benefits in exertional dyspnoea and exercise tolerance [26].…”
Section: Long-acting B 2 -Agonistsmentioning
confidence: 99%
“…Although LABAs reduced the use of rescue medication in the majority of studies, the efficacy of these agents on dyspnoea is not consistent across trials and significant benefits on exercise tolerance have not been well described (table 1) [9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, a recent, small-scale (23 patients), mechanistic, crossover study showed that salmeterol significantly reduced hyperinflation, with consequent benefits in exertional dyspnoea and exercise tolerance [26].…”
Section: Long-acting B 2 -Agonistsmentioning
confidence: 99%
“…Patients continued on ipratropium bromide 40 mg four times daily and were randomized to either salmeterol (50 mg twice daily) or placebo as add-on therapy. The investigators found evidence of significantly improved airflow in the salmeterol group compared with placebo at 4, 8, 16, and 24 weeks after the initiation of therapy (38). While the salmeterol group had fewer acute exacerbations of COPD (26% versus 33%), the results did not reach statistical significance (P 5 0.117).…”
Section: Long-acting B-agonists and Short-acting Anticholinergicsmentioning
confidence: 95%
“…The use of LABAs in combination with short-acting anticholinergics has been examined in several studies (37)(38)(39). van Noord and colleagues performed a 12-week multi-centered, randomized, double-blind trial in 144 patients with moderate-severe COPD (mean age 65; mean FEV 1 44% of predicted) (37).…”
Section: Long-acting B-agonists and Short-acting Anticholinergicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent meta-analyses have shown that tiotropium consistently reduced hospitalization rates in moderate-to-severe COPD (2,3). Pooled analyses, including such recent studies as TORCH (Towards a Revolution in COPD Health) (4), were conducted to update previous studies, and tiotropium is still the only inhaled therapy that consistently and significantly reduced hospitalizations (Forest plots are available at http://pulmccm.blogspot.com) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although the TORCH study showed a statistically significant reduction in hospitalizations with combined LABA and inhaled corticosteroid therapy, not enough data are available to conduct a pooled analysis on COPD-related hospitalizations.…”
Section: Does Tiotropium Reduce Hospitalizations In Chronic Obstructimentioning
confidence: 99%